First report on containers - Kay, E.; Pemberton, A. W. (College of Aeronautics, 1966)
Everybody agrees that containers are a "good thing";the actual advantages of transporting cargo, and in particular, dry cargo, in containers over other forms of transport have, to our knowledge, nowhere been stated in quantitative terms. It is claimed that containers will reduce the turn-round time of ships, ease congestion in the docks, speed-up total transit time of cargo, reduce the risk of pilferage, reduce packaging cost and reduce total handling effort in all stages of transit. Given that all these advantages are real, it is obvious that they do not accrue in equal measure to all parties concerned in the movement of goods from consignor to consignee. There is indeed a likelihood of a conflict of interest between these parties. In this report we shall try to delineate the various problem areas, indicate the quantitative information that needs to be collected in order to decide how to solve these problems and outline an approach to such solutions.